Pengaruh Pemberian Kompres Serai Terhadap Nyeri Arthritis Rheumatoid pada Lansia di Wilayah Kerja Puskesmas Kuta Baro Kabupaten Aceh Besar - Sri Wahyuni; Syukriadi Syukriadi; Irma Andriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The prevalence of rheumatoid arthritis in the world has doubled. The aim of the research was to determine the effect of giving lemongrass compresses on rheumatoid arthritis pain in the elderly in the Kuta Baro Health Center Working Area, Aceh Besar Regency. This research method uses a quasi-experimental design with a one group pretest-posttest approach with a population of 317 people and a sample size of 15 people, the sampling technique is purposive sampling. This research was conducted from 30 May to 6 June 2024 using univariate and bivariate analysis using the Paired T test. The results of the study showed that before being given the lemongrass warm compress the average pain level of the respondents was 4.60, whereas after being given the lemongrass warm compress the average pain level was 2.53 with a decrease of 2.067 with a ρ value of 0.000, meaning there was a relationship with the lemongrass warm compress with rheumatoid arthritis pain in the elderly. The conclusion is that there is an effect of warm lemongrass compresses on rheumatoid arthritis pain in the elderly because warm lemongrass compresses have a positive impact on reducing rheumatoid arthritis pain in the elderly. It is hoped that rheumatoid arthritis sufferers will carry out non-pharmacological therapy using lemongrass if their pain scale is still in the mild and moderate category.